Pequenos jogos no futebol: comportamento tático e perfil motor em superioridade numérica - Gibson Moreira Praca (2014)
Soccer small-sided games have been used as tools during the training process because they replicate the 11vs.11 technical, tactical, physical and physiological demands. In this sense, studies have verified demands through pitch size, number of players and ball touches allowed per possession manipulating. However, these studies have been using configurations with equal number of players between the teams, and a little attention has been paid to study unbalanced teams situations. This study aimed to compare tactical individual, collective and time-motion characteristics of three soccer small-sided games configurations: equal number of players, additional player into the game field and two additional players on the side of the game field. Eighteen male young soccer players participated in a 4-week study. In the first week they performed a Tactical Procedural Knowledge test a criteria to the team formation and two familiarization sessions. During the 2-4 weeks they performed nine sessions of small-sided games, three in each configuration. Each session was composed by four small-sided games with four minutes of duration and four minutes of passive rest. The teams formation were conducted using two criteria: playing position (defenders, midfielders and forwards) and the performance on Tactical Procedural Knowledge test performed at the first day. At the ending, six teams were formed. Tactical individual behavior were assessed through the FUT-SAT protocol, and the tactical collective was assessed through the positional data from 15Hz GPS devices. The same equipment was used to access the time-motion characteristics, related to the distance travelled total and intervals of speed and accelerations total actions and distance dispended in actions of acceleration. Inter and intra reliability protocols was conducted for the FUT-SAT itens. The individual tactical behavior was analyzed through the chi-square test. For the collective tactical behavior and time-motion characteristics, normality tests were conducted (Kolmogorov-smirnov for the first and Shapiro-wilk for the second). From these results, it was decided to use the Friedmans non parametric test to compare the collective tactical behavior and One-way ANOVA with repeated measures to compare time-motion characteristics. Effect size calculations were performed to each variable. Results showed higher incidence of without ball tactical principles in additional players games than in games with equal number of player, while these last configuration presented a higher incidence of Penetration actions. Additional players games decreased the physical demand, with lower values of total distance travelled, distance travelled in higher speeds, distance in acceleration and number of accelerations than games with equal number of players. Additional players into the game fields games elicited more behaviors associated with width and length positioning than games with equal number of players, while games with additional players out of the game field presented bigger values of centroide distance and length per width ratio (lpwratio). Results indicate differences in tactical individual and collective behavior and time-motion characteristics in small-sided games performed with equal number of players and additional players into the game field and out of the game field. It is suggested that coaches and physical trainers choose those games that are best suited to the purpose of the session. Specifically, games with additional players are recommended to improve tactical skills, mainly without ball actions, and games with equal number of athletes between the teams are best recommended to improve the physical demand of the training session.